2014
DOI: 10.1155/2014/342012
|View full text |Cite
|
Sign up to set email alerts
|

Balance Ability and Proprioception after Single-Bundle, Single-Bundle Augmentation, and Double-Bundle ACL Reconstruction

Abstract: Purpose. The present study sought to determine the influences of single-bundle (SB), single-bundle augmentation (SBA), and double-bundle (DB) reconstructions on balance ability and proprioceptive function. Methods. 67 patients who underwent a single- or double-bundle ACL reconstruction or a SBA using multistranded autologous hamstring tendons were included in this study with a 1-year follow-up. Body sway and knee kinesthesia (using the threshold to detect passive motion test (TTDPM)) were measured to indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Proprioception of the ACL is closely related to knee joint stability, which is realised through feedback regulation of the central nervous system; however, the key node on the pathway remains unknown [ 27 30 ]. Many studies confirmed that when the ACL proprioception function is decreased, the neural feedback regulation pathway is bound to be disordered; therefore, it could have further impact on the proprioception function [ 31 , 32 ]. Some studies showed that NT-3 was the key induced signal of proprioceptive transduction; when NT-3 expression was normal, the proprioceptive nerve fibres could control the target organs and have physiological roles [ 33 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proprioception of the ACL is closely related to knee joint stability, which is realised through feedback regulation of the central nervous system; however, the key node on the pathway remains unknown [ 27 30 ]. Many studies confirmed that when the ACL proprioception function is decreased, the neural feedback regulation pathway is bound to be disordered; therefore, it could have further impact on the proprioception function [ 31 , 32 ]. Some studies showed that NT-3 was the key induced signal of proprioceptive transduction; when NT-3 expression was normal, the proprioceptive nerve fibres could control the target organs and have physiological roles [ 33 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…2) (9). A single-bundle reconstruction is performed by producing one single femoral tunnel and one single tibial tunnel, with focus on reproducing the AM bundle.…”
Section: Surgical Techniques and Surgical Navigation Terminologymentioning
confidence: 99%
“…A single-bundle reconstruction is performed by producing one single femoral tunnel and one single tibial tunnel, with focus on reproducing the AM bundle. The selective single-bundle augmentation reconstruction is focused on AM or PL bundle repair with preservation of the remaining intact bundle, while the double-bundle reconstruction uses two separate grafts to replace the positioning of both the AM and PL bundles (9). An anatomic double-bundle, four-tunnel reconstruction using the double-bundle technique has the potential to restore the biomechanics of the knee better than the classic single-bundle, two-tunnel technique (Fig.…”
Section: Surgical Techniques and Surgical Navigation Terminologymentioning
confidence: 99%
“…Although anterior cruciate ligament (ACL) reconstructions are routinely performed to treat ACL injuries, these injuries may have serious consequences [ 1 ]. Double-bundle, single-bundle (SB) augmentation and SB techniques are widely practiced to reconstruct the ACL [ 2 ]. The double-bundle and SB augmentation techniques are also referred to as anatomic double-bundle and anatomic SB techniques respectively.…”
Section: Introductionmentioning
confidence: 99%